2019
DOI: 10.1002/pssb.201800640
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Expansion Studies on the Spin‐Liquid‐Candidate System κ‐(BEDT‐TTF)2Ag2(CN)3

Abstract: This paper presents results of the thermal expansion coefficient of the newly‐synthesized spin‐liquid‐candidate system κ‐(BEDT‐TTF)2Ag2(CN)3. The main finding includes pronounced broad extrema in the electronic contribution to the thermal expansion at T ≈ 18 K along all three crystallographic directions which is assigned to the effect of strong electronic correlations. The observed anomalies are qualitatively consistent with recent theoretical results based on the Hubbard model on a triangular lattice (J. Koka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Difficulties with the crystal growth complicated a more circumstantial investigation of the QSL candidate κ-(BEDT-TTF) 2 Ag 2 (CN) 3 -only two groups (Hiramatsu/Yoshida/Saito [39,40] and Hübner/Dressel [45]) have succeeded to synthesize it so far. Here, dilatometric experiments revealed an anisotropic structural anomaly around 11 K [119] reminiscent of Figure 6a. In view of the gapped excitations concluded from thermal transport experiments [95,96], thermal expansion studies on EtMe 3 -Sb[Pd(dmit) 2 ] 2 may provide useful information.…”
Section: Discussionmentioning
confidence: 59%
“…Difficulties with the crystal growth complicated a more circumstantial investigation of the QSL candidate κ-(BEDT-TTF) 2 Ag 2 (CN) 3 -only two groups (Hiramatsu/Yoshida/Saito [39,40] and Hübner/Dressel [45]) have succeeded to synthesize it so far. Here, dilatometric experiments revealed an anisotropic structural anomaly around 11 K [119] reminiscent of Figure 6a. In view of the gapped excitations concluded from thermal transport experiments [95,96], thermal expansion studies on EtMe 3 -Sb[Pd(dmit) 2 ] 2 may provide useful information.…”
Section: Discussionmentioning
confidence: 59%
“…In fact, κ-CuCN has been considered for a long time as a prime candidate for the realization of a quantum spin liquid [10,46] that potentially hosts gapless excitations [47]. However, thermal expansion measurements [48,49] indicate the presence of a phase transition around 6 K, often referred to as the "6 K anomaly", which might prevent the formation of a possible spin-liquid phase. In recent years, the interpretation of magnetic torque [8] and NMR [50] data suggested that a valence-bond solid rather than a quantum spin liquid might be formed in κ-CuCN [12] below T * ∼ 6 K. This picture was further supported by recent ESR studies confirming the presence of a spin gap opening [34] around the 6 K anomaly.…”
Section: Phase Diagrammentioning
confidence: 99%
“…A prominent example is the electronic nematic phase which is believed to be ubiquitous to the phase diagrams of many high-temperature superconductors [114][115][116] and which is intimately coupled to lattice instabilities [117][118][119]. In addition, the coupling to the lattice has received increasing levels of attention in the field of organic [34,49,87,120,121] and inorganic frustrated magnets [122][123][124][125][126][127][128].…”
Section: Coupling Of Correlated Electrons To the Crystal Latticementioning
confidence: 99%